THE ROLE OF LOCALIZATION IN SUPPORTING LARGE-SCALE AUTOMOBILE PRODUCTION: THE CASE OF UZBEKISTAN (Multidisciplinary Journal of Science and Technology, 2026)
This paper examines the role of localization in reaching high production volumes in the automotive industry, focusing on Uzbekistan’s experience. The study analyzes the challenges of achieving one million vehicles production per year under the condition of high logistics costs and dependance on imported parts. A benchmark analysis of countries producing one million passenger cars annually shows that such scale has been achieved by a limited number of countries in the world and is not directly related to country’s population size or GDP per capita. Instead, vehicle affordability, access to export markets and lower costs are more important. The paper also demonstrates that reliance on imported parts significantly increases production costs due to long lead times, warehousing expenses and freezing working capital, especially in landlocked countries. The findings in the paper suggest that localization of component manufacturing is necessary condition to support high-scale production.